2013
DOI: 10.1016/j.pediatrneurol.2013.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Automatically Quantified Diffuse Excessive High Signal Intensity on MRI Predicts Cognitive Development in Preterm Infants

Abstract: Background Cognitive and language impairments constitute the majority of disabilities observed in preterm infants. It remains unclear if diffuse excessive high signal intensity (DEHSI) on MRI at term represents delayed white matter maturation or pathology. Methods We hypothesized that diffusion tensor imaging-based objectively quantified DEHSI measures at term will be strong predictors of cognitive and language development at 2 years in a cohort of 41 extremely low birth weight (ELBW; ≤1000g) infants. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 38 publications
(62 reference statements)
1
37
0
Order By: Relevance
“…These findings suggest that we must exercise caution in relying on MRI as a key predictor of NDI[23, 24]. In our cohort, the inability of WM abnormalities to predict outcomes other than CP was true irrespective of the scoring system we employed.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These findings suggest that we must exercise caution in relying on MRI as a key predictor of NDI[23, 24]. In our cohort, the inability of WM abnormalities to predict outcomes other than CP was true irrespective of the scoring system we employed.…”
Section: Discussionmentioning
confidence: 94%
“…We speculate that defining the presence, type, and degree of WM abnormality on qualitative MRI is subjective and this contributes to our inability to predict cognitive or language outcomes. Furthermore, conventional MRI is less sensitive in diagnosing delayed/aberrant brain development and microstructural abnormalities that are likely common contributors to cognitive and language development[24]. Beyond conventional MRI data, advanced applications of MRI may prove to be more helpful in predicting outcomes, along with other forms of neurologic assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies found a strong association between volume of DEHSI and cognitive and language scores on the Bayley-III at 2 years of age. 41,65 …”
Section: Resultsmentioning
confidence: 99%
“…41,65 Four additional studies that examined the centrum semiovale also found a significant correlation between diffusion metrics or brain NAA/Choline and cognitive and language scores at 18–24 months CA. 35,50,54,60 This finding is in distinct contrast to studies that have qualitatively evaluated DEHSI and found no association with outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…While connectivity for such long-range networks is expected to be lower, subtle and diffuse brain abnormalities such as diffuse excessive high signal intensity abnormalities may also be contributing to the lower connectivity observed in these regions. Such abnormalities are observed in up to 75-80% of very preterm infants and appear to be associated with cognitive and language deficits [47,48]. It is not yet known if infants with diffuse excessive high signal intensity abnormalities exhibit early maturational delays in executive and frontoparietal networks.…”
Section: Discussionmentioning
confidence: 99%